Testing of the Serbian version of the Oral Health Impact Profile-14 (OHIP-14) questionnaire among professional members of the Serbian Armed Forces - Lekić, Margareta; Daković, Dragana; Kovačević, Vladan; Čutović, Tatjana; Ilić, Irena; Ilić, Milena (Vojnosanitetski pregled, 2022)
Background/Aim. The quality of life regarding oral health is a multidimensional concept that shows to which extent oral diseases and disorders impact the quality of life of each individual. One of the most frequently used questionnaires for testing the impact of oral health on the quality of life is the Oral Health Impact Profile-14 (OHIP-14). The aim of this study was to test the short form of the OHIP-14 questionnaire among professional members of the Serbian Armed Forces. Methods. A cross-sectional design was applied in this study. The reliability of the questionnaire was determined by Cronbach’s coefficient alpha. The validity of the OHIP-14 questionnaire was assessed by the factor analysis. Results. A total of 1,611 participants, professional members of the Serbian Armed Forces, with a mean age of 33.5, agreed to participate in the study (the participation rate was 97.4%). The majority of the participants were males (88.8%). The overall Cronbach’s alpha coefficient of the OHIP-14 scale was 0.960. The alpha reliability coefficients of all OHIP-14 subscales were between 0.732 and 0.865, indicating that the internal consistency reliability of all subscales was good. The Principal components analysis, same as inspection of the scree plot and parallel analysis supported a one-factor solution for the OHIP-14 scale. Conclusion. The OHIP-14 manual is equally reliable for determining the impact of oral health on the quality of life of professional members of the Serbian Armed Forces as it is with the civilian population.